Online information system on coconut product processors in Southern Mindanao - Tolentino, Rheena Quevedo (2005)
This online information system shows the company profiles and the products produced by the coconut products processors in Southern Mindanao. It also shows the raw materials that these processors need. It has three main users the administrators, the processors and the people that will visit the site. It allows the users to look through important information regarding the coconut processing industry in Southern Mindanao. The system has an online registration for processors who would like their companies to be included in the database of this system and they can update their profiles online. Added is a forum wherein visitors of the site can discuss issues regarding the coconut industry. This system includes a coconut industry report for Southern Mindanao. It also contains statistical reports on the processors in Region XI, the volume of the production of a particular coconut product per province and per processor of a specific province. The system administrator can add, update and delete the information online. This online information system is beneficial to the different stakeholders of the industry
Thesis (BS Computer Science) -- University of the Philippines Mindanao, 2005
Keywords: Software design; Coconut products processors; Coconut products processors -- Southern Mindanao